2017
DOI: 10.1152/jn.00123.2017
|View full text |Cite
|
Sign up to set email alerts
|

Separable systems for recovery of finger strength and control after stroke

Abstract: Impaired hand function after stroke is a major cause of long-term disability. We developed a novel paradigm that quantifies two critical aspects of hand function, strength, and independent control of fingers (individuation), and also removes any obligatory dependence between them. Hand recovery was tracked in 54 patients with hemiparesis over the first year after stroke. Most recovery of strength and individuation occurred within the first 3 mo. A novel time-invariant recovery function was identified: recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
140
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(166 citation statements)
references
References 57 publications
17
140
0
1
Order By: Relevance
“…An SAS can augment the magnitude of voluntary muscle contraction in control subjects and Parkinson's patients (Anzak et al, 2011a, b). In stroke patients, the recovery of strength might involve strengthening of non-corticospinal pathways, such as the reticulospinal tract (Xu et al, 2017). We argue that this may be different in spastic muscles of SCI participants because we observed smaller MVCs in the quadriceps muscle in people with higher reticulospinal gain.…”
Section: Functional Considerationsmentioning
confidence: 73%
“…An SAS can augment the magnitude of voluntary muscle contraction in control subjects and Parkinson's patients (Anzak et al, 2011a, b). In stroke patients, the recovery of strength might involve strengthening of non-corticospinal pathways, such as the reticulospinal tract (Xu et al, 2017). We argue that this may be different in spastic muscles of SCI participants because we observed smaller MVCs in the quadriceps muscle in people with higher reticulospinal gain.…”
Section: Functional Considerationsmentioning
confidence: 73%
“…The data showed good reliability for the major dependent variable, IHI ratio ( α = 0.74 and 0.79 for patients and controls, respectively; Participants and Methods). Figure shows the distribution of lesions defined using diffusion tensor images (details reported in our earlier publication).…”
Section: Resultsmentioning
confidence: 99%
“…Our cohort of patients was mild to moderately impaired in the acute stage (FMA INITIAL Mean = 41 ± 22; Table ). Motor recovery was quantified using three behavioral measures: FMA, Strength and an Individuation Index for finger (ability to move digits independently; Participants and Methods) . All three measures showed good early recovery (Strength: χ 2 = 28.07; p < 0.001, Individuation: χ 2 = 13.64; p < 0.001, and FMA: χ 2 = 28.07; p < 0.001), but then plateaued after the subacute stage (Fig ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results also have 199 implications for rehabilitation of individual finger movements after stroke. The strength and 200 coordination of individual finger movements are impaired after stroke, recovering significantly 201 through the first year post-stroke but often leaving chronic deficits (Xu et al, 2017). Recent work 202 has suggested that this recovery and subsequent chronic impairment can be tracked through 203 MVPA of individual finger representations (Xu et al, 2015), although the to-date published results 204 of the fMRI data from this study report only average region-of-interest analyses (Ejaz et al,205 2018).…”
Section: Differential Modulation Of Finger Preferencementioning
confidence: 99%